2020
DOI: 10.3390/cancers12040881
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Enriched with Moonlighting Metalloproteinase Are Highly Transmissive, Pro-Tumorigenic, and Trans-Activates Cellular Communication Network Factor (CCN2/CTGF): CRISPR against Cancer

Abstract: Matrix metalloproteinase 3 (MMP3) plays multiple roles in extracellular proteolysis as well as intracellular transcription, prompting a new definition of moonlighting metalloproteinase (MMP), according to a definition of protein moonlighting (or gene sharing), a phenomenon by which a protein can perform more than one function. Indeed, connective tissue growth factor (CTGF, aka cellular communication network factor 2 (CCN2)) is transcriptionally induced as well as cleaved by MMP3. Moreover, several members of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 71 publications
1
63
0
Order By: Relevance
“…Earlier studies showed that MMPs constituted a large family of zinc/calcium-dependent endopeptidases, playing key roles in extracellular matrix (ECM) remodeling because of their ability to degrade numerous components of ECM (such as collagens and proteoglycans) and non-ECM proteins (such as adhesion molecules, cytokines, protease inhibitors, and membrane receptors) [24]. Later studies have shown that matrix metalloproteinase 3 (MMP3) was a bifunctional protein that acted as a proteolytic enzyme and a transcriptional factor, playing crucial roles in tumor progression [30][31][32]. Therefore, we defined MMP3 as a moonlighting protein, as it plays multiple roles in the cells as a proteinase as well as a transcription factor [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies showed that MMPs constituted a large family of zinc/calcium-dependent endopeptidases, playing key roles in extracellular matrix (ECM) remodeling because of their ability to degrade numerous components of ECM (such as collagens and proteoglycans) and non-ECM proteins (such as adhesion molecules, cytokines, protease inhibitors, and membrane receptors) [24]. Later studies have shown that matrix metalloproteinase 3 (MMP3) was a bifunctional protein that acted as a proteolytic enzyme and a transcriptional factor, playing crucial roles in tumor progression [30][31][32]. Therefore, we defined MMP3 as a moonlighting protein, as it plays multiple roles in the cells as a proteinase as well as a transcription factor [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have shown that matrix metalloproteinase 3 (MMP3) was a bifunctional protein that acted as a proteolytic enzyme and a transcriptional factor, playing crucial roles in tumor progression [30][31][32]. Therefore, we defined MMP3 as a moonlighting protein, as it plays multiple roles in the cells as a proteinase as well as a transcription factor [32,33]. It has been shown that some members of MMPs were expressed at high levels in particular cancer types and promoted tumor progression.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations